Plasma Waves Can Gain Energy from Neutrals in Partially Ionized Plasmas - Junnan Jiang; Yu Liu; Wenlong Huang; Minchi Li; Rong Jin; Pengcheng Yu; Jiuhou Lei (The Astrophysical Journal)
Partially ionized plasmas are widely present in astrophysical and space plasmas, and ion-neutral collisions have an important impact on the plasma dynamics, such as electrostatic wave propagation. In this work, the excitation and propagation characteristics of electrostatic ion cyclotron (EIC) waves were experimentally studied in a partially ionized plasma. The EIC waves were launched via a grid antenna, and two types of EIC waves were observed to be excited and propagated. In partially ionized plasmas with weak ion–neutral collisions, it was found that the EIC wave propagation is dominated by ion motion, resembling the classical EIC wave. However, in plasmas with strong ion–neutral collisions, experiments revealed for the first time that EIC wave propagation can be dominated by neutral motion, which leads to an increase in the collisional EIC wave’s phase velocity. Additionally, the EIC wave dispersion relationships under collisions were determined to reveal the underlying processes responsible for the observations. This work verified that collisional EIC waves can gain energy from neutrals in partially ionized plasmas, which suggests that ion‒neutral collisions in the Earth and planetary ionosphere and solar atmosphere have a more complex impact on plasma wave propagation than previously thought.